The Role of Social Media as a Means of Mass Communication in Influencing the Consumptive Behavior of Padang City Residents - Erningsih, Erningsih; Izzati, Fahira Nur; Husna, Syarifatul; Saputra, Syahrizal Praditya; Syahira, Vaura; Meiwahyu, Veni (Journal of Humanity Studies, 2024)
Social media is now not only a mass communication tool but also a means of massively and rapidly shaping people's consumption patterns. In Padang City, the increase in social media use has triggered significant changes in consumer behavior, particularly among the younger generation. The emerging issues are not only related to impulsive consumption but also to individuals' increasing reliance on social media as a primary reference in determining consumption needs. This phenomenon raises concerns about the blurring of the line between real needs and digitally constructed desires. Using a descriptive quantitative approach, the data in this study were obtained through literature review and interviews with 30 respondents aged 18–40 who actively use social media for at least 2 hours per day. The results indicate that platforms such as Instagram and TikTok play a significant role in influencing purchasing decisions, particularly through promotional content and viral trends. These findings confirm that social media is a crucial actor in shaping urban consumer culture. Therefore, strengthening digital literacy and education on healthy consumption are needed to enable the public to respond wisely to social media exposure. Keywords: digital consumption, mass communication, social media, consumer behavior, visual trends